On some novel solitons solutions to the generalized (3+1)-dimensional Boiti-Leon-Manna-Pempinelli model using two different approaches - Tariq, K. U.; İnç, Mustafa; Javed, R. (Soc Mexicana Fisica, 2022)
In this study we investigate Boiti-Leon-Manna-Pempinelli equation in three dimensions, which describes the evolution of the horizontal velocity component of water waves propagating in the xy-plane in an infinite narrow channel of constant depth and that can be considered as a model for incompressible fluid. The new (F/G)-expansion approach and the unified approach are employed to construct some new traveling wave solutions to the nonlinear model. A large numbers of traveling wave solutions for the nonlinear model are demonstrated respectively in the form of hyperbolic and trigonometric function solutions. The proposed methods are also proved to be effective in solving nonlinear evolution problems in mathematical physics and engineering.
Keywords: New (F; G)-expansion method; the unified method; traveling waves solutions; nonlinear evolution equations; exact solutions